(untitled) (Journal of Educational Sciences, 2016)
In the article the results of the first phase of the study grant №1763/ GF4 “Development of creativity and creative abilities of students as the factor of the intellectual potential of Kazakhstan” of MES of RK were demonstrated. The concepts of “creativity”, “creative abilities”, “educational environment of the university” were considered. The concepts of “creativity” and “creation” were compared, the theoretical basis for the development of creativity in the form of a scheme including the phases of development of creativity, stages of formation, approaches to learning, external and internal factors influencing the creativity of the individual were systematized. A model of development of creativity of students in the educational environment of the university was designed. The model consists of objectives and tasks, principles of creativity development, content and methods, students’ creativity development program, results. The results of experimental pedagogical work on the testing model and program of creativity development, in which 40 students of pedagogical specialties Al-Farabi KazNU took part.